2013
DOI: 10.1089/bfm.2012.0153
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding in Obstetrics Residency: Exploring Maternal and Colleague Resident Perspectives

Abstract: Despite high levels of perceived support from faculty/fellow residents, breastfeeding residents struggle with low milk supply and work demands that lead to early discontinuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 12 publications
2
27
0
Order By: Relevance
“…Consistent with other physician studies, [9][10][11][12][13][14][23][24][25][26] we found high breastfeeding initiation rates in this study. We note that the breastfeeding rates in this study surpass those of the general population and meet the Healthy People 2020 breastfeeding objectives.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with other physician studies, [9][10][11][12][13][14][23][24][25][26] we found high breastfeeding initiation rates in this study. We note that the breastfeeding rates in this study surpass those of the general population and meet the Healthy People 2020 breastfeeding objectives.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with other physician studies, [14][15][16][17][19][20][21][22] we found high breastfeeding initiation rates among the 72 physician mothers in the IM cohort. It is encouraging that more than one half of the infants in this study were able to continue receiving breast milk at 6 months of age and that there was a statistically significant correlation between maternal goal for breastfeeding duration and actual breastfeeding duration.…”
Section: Discussionsupporting
confidence: 91%
“…While our study cohort might have been too small for detection of significant relationships between work-related factors and breastfeeding duration, previous physician studies have identified lack of time and place for breastfeeding/ milk expression, lack of collegial or attending support, and inadequate milk supply after return to work as work-related obstacles to breastfeeding maintenance. [14][15][16][17][19][20][21][22][23] Programs to promote breastfeeding duration, including formal maternity leave policies, part-time employment opportunities, longer paid maternity leave, nonclinical duties when physician mothers first return to work, on-site childcare facilities, protected time for milk expression at work, designated lactation rooms and sanitary storage for breast milk, as well as support and reinforcement at the work-site, especially from colleagues, program directors, and chiefs, are modifiable institutional factors that might influence IM physician mothers' breastfeeding duration after return to work. Effective workplace strategies to promote breastfeeding duration among IM physician mothers returning to work might not only improve the health of the physicians and their children but also enhance their role as breastfeeding advocates and improve breastfeeding rates in the community.…”
Section: Resultsmentioning
confidence: 99%
“…The benefits of breastfeeding for mother and child are well established, such as a reduction in serious upper respiratory infections by 63% in infants who breastfed for 6 months, a 36% reduction in SIDS (sudden infant death syndrome), reductions in childhood lymphoma and leukemia correlated with duration of breastfeeding, and even improved neurodevelopmental outcomes . These benefits led to clear recommendations from the American Academy of Pediatrics and the World Health Organization of, “exclusive breastfeeding for about 6 months, followed by continued breastfeeding as complementary foods are introduced, with continuation of breastfeeding for 1 year or longer as mutually desired by mother and infant.” Our policy is also intended to protect against dwindling milk supply in breastfeeding mothers by creating adequate opportunities for lactation . However, in a 2018 JAMA research letter, less than one‐third of physicians report adequacy of breastfeeding according to their personal goal.…”
Section: Discussionmentioning
confidence: 99%